Strategi Kepala Madrasah Dalam Pembentukan Budaya Religius di MA Ma’arif 1 Jombang - Qusyaeri, Ahmad; Rozikin, Hari Khoirur (LP3M STIT Al Urwatul Wutsqo Jombang, 2022)
The strategy of the Head of the Madrasa in the formation of religious culture is an effort made by the Head of the Madrasa to create the religious character of students through habituation of religious activities in the madrasa. The habituation of religious cultural activities in students can increase faith, and piety, and increase understanding of religious teachings in everyday life. This thesis aims to: (1) describe the strategy of the head of Madrasah in the formation of religious culture in MA Ma'arif 1 Jombang, and (2) describe the variety of religious cultures in MA Ma'arif 1 Jombang. This study uses qualitative research methods, using a descriptive approach. Collecting data through in-depth interviews, participant observation, and documentation. Checking the validity of the data is done through the extension of participation, the persistence of observation, and data triangulation. The results of data analysis found that: (1) The strategy of the Head of Madrasah in the formation of religious culture in MA Ma'arif 1 Jombang includes: the first, holding structured and scheduled activities. strategy second hold routine activities. strategy third holds activities that are incidental in nature. (2) Religious culture at MA Ma'arif, including commemoration of Islamic holidays (PHBI), the addition of MULOK lessons, such as ASWAJA, BTQ (Read Write the Qur'an), BBK (Book Reading Guidance), every morning students You are required to participate in a prayer together, at the beginning of the hour you are required to pray together, as well as at the end it is closed with a prayer together, dluha prayer, zuhr prayer in congregation, istighosah, tadarus and so on.